Development of kraft paper reinforced with bleached cellulosic nanofibrils for application in packaging - Lima, Lidiane Costa (2019)
The first study aimed to establish physical and mechanical contribution of cellulose nanofibrils to the resistance of packaging papers, determine nanofibrils interaction with the fibrous matrix and its potential to allow grammage reduction without paper resistance downsizing. Paper sheets were prepared by mixing unbleached Eucalyptus fibers and cellulose nanofibrils from mechanical defibrillation, following the standardized steps: homogenizing, vacuum filtration, pressing and room temperature drying. The twelve treatments resultants from the combination of the final grammages 75, 85, 95 and 105 g/m² with the nanofibril concentrations of 1, 5 and 10 wt% were analyzed to determine physical and mechanical properties, along with FEG-SEM images to investigate paper formation and nanofibrils accommodation within the paper. Micrographs showed the formation of nanofilms and aggregations between nanofibrils and fibers/microfibers within the paper, causing reduction in paper porosity and consequent increase in resistance to air passage. Results showed that nanofibrils reinforcement contribute to enhance all properties analyzed, except for corrugating medium test, only influenced by grammage, water vapor permeability and water vapor transmission rate, that presented no tendency. Resistance to air passage, tensile index, stretch and modulus of elasticity stand out for improvements being result only of the cellulose nanofibril reinforcement, with no influence of grammage, proving the effectiveness of cellulose nanofibrils to enhance barrier properties and mechanical resistance even with grammage reduction. The second study aimed to investigate near infrared spectroscopy capability to estimate nanofibrils content, physical and mechanical properties of packaging papers reinforced with cellulose nanofibrils. Principal component analysis (PCA), partial least squares (PLS) and partial least squares discriminant analysis (PLS-DA) based on laboratorial and spectral information were utilized. At PCA there was no separation between specimens related to nanofibril content. PLS generated models for nanofibrils content, tensile index, stretch and resistance to air passage with R²cv range from 0.73 to 0.98, indicating that NIRS technique is suitable for predicting physical and mechanical properties of packaging papers and can detect cellulose nanofibril into the paper matrix. PLS-DA models correctly classify more than 98% of the samples according to nanofibril content.